2017
DOI: 10.1186/s12963-017-0127-3
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of pre-injury health-related quality of life: a systematic review

Abstract: BackgroundInsight into the change from pre- to post-injury health-related quality of life (HRQL) of trauma patients is important to derive estimates of the impact of injury on HRQL. Prospectively collected pre-injury HRQL data are, however, often not available due to the difficulty to collect these data before the injury. We performed a systematic review on the current methods used to assess pre-injury health status and to estimate the change from pre- to post-injury HRQL due to an injury.MethodsA systematic l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
43
1
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(49 citation statements)
references
References 56 publications
(324 reference statements)
3
43
1
2
Order By: Relevance
“…It is a common occurrence that injury victims report pre-injury HR-QoL that exceeds age-speci c population norms (30). In our study, this was, however, only apparent in patients with negative BAL, whereas in patients with positive BAL we noticed the opposite.…”
Section: Discussioncontrasting
confidence: 66%
“…It is a common occurrence that injury victims report pre-injury HR-QoL that exceeds age-speci c population norms (30). In our study, this was, however, only apparent in patients with negative BAL, whereas in patients with positive BAL we noticed the opposite.…”
Section: Discussioncontrasting
confidence: 66%
“…One limitation of the study stems from the impossibility of obtaining information prospectively on the prefracture situation, and therefore assuming the possibility of memory bias and underestimation of the results [47]. HRQoL in patients after hip fracture may be influenced by other unrelated factors such as pre-existing comorbidities [48].…”
Section: Discussionmentioning
confidence: 99%
“…This is because individuals from the general population are unlikely to be representative of those from an injured population [68]. A systematic review of studies collecting pre-injury HRQL data among injury patients has demonstrated that both general population comparisons and retrospective assessments are likely to result in biased estimates of preinjury HRQL [69]. However, prospective HRQL data is often impractical to collect prior to an injury occurring.…”
Section: Discussionmentioning
confidence: 99%